2022
DOI: 10.1093/ehjopen/oeac065
|View full text |Cite
|
Sign up to set email alerts
|

The risk of cardiovascular diseases after miscarriage, stillbirth, and induced abortion: a systematic review and meta-analysis

Abstract: Aims Miscarriage and stillbirth has been included in cardiovascular disease (CVD) risk guidelines, however heterogeneity in exposures and outcomes and the absence of reviews assessing induced abortion, prevented comprehensive assessment. We aimed to perform a systematic review and meta-analysis of the risk of cardiovascular diseases for women with prior pregnancy loss (miscarriage, stillbirth and induced abortion). Methods and Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…In addition, we have identified a risk-conferring impact of history of abortion on the odds of cardiometabolic disease. Evidence from a recent meta-analysis showed that women with previous pregnancy loss were at high risk for cardiovascular disease and stroke in later life ( 36 ), which consolidated our observations.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, we have identified a risk-conferring impact of history of abortion on the odds of cardiometabolic disease. Evidence from a recent meta-analysis showed that women with previous pregnancy loss were at high risk for cardiovascular disease and stroke in later life ( 36 ), which consolidated our observations.…”
Section: Discussionsupporting
confidence: 85%
“…However, the strengths of this study are: (1) Having a strict inclusion criterion for each clinical entity; and (2) Evidence-based detailing on the clinical profile and the outcome of each described complication. As per the authors’ knowledge, there are previous studies done including Kyriacou et al [ 3 ] who have reported that women with previous pregnancy loss, following a miscarriage, stillbirth, and induced abortion, are at higher risk of coronary heart disease and stroke. However, this is the first review detailing the clinical profile, imaging details, complications, and outcomes of the various CVD complications following MTP.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, having an understanding of the female specific risk stratification and prevention is important. Recent CVD risk guidelines have included miscarriage and stillbirth as risk factors for women[ 3 ]. Because of the changing times and laws, we must highlight various CVD complications which are associated with the termination of pregnancy[ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Past reviews have attempted to elucidate the association between a prior early pregnancy loss and the subsequent development of cardiovascular disease, 77 , 78 , 79 without attention to intermediary factors, such as diabetic and hypertensive disorders. This review undertook a comprehensive review of the findings from observational studies that investigated the association between a prior early pregnancy loss and the subsequent risk of developing a diabetic or hypertensive disorders, some of which are modifiable and can thereby prevent the onset of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%